Eliciting Awe in the Spectator: The Case of a Dhrupad-Based Dance Performance. - Santarpia, Alfonso; Martin, Andrée; Menicacci, Armando; De Oliveira, Pierre; Lemieux, Daniel; Éthier, Laurence; Charbonneau, Caroline; Pucella, Bruno; Flambard, Christophe; Gundecha, Les Frères; Lusignan, Louis-Charles; Bourgasser, Alice; et al. (International Journal of Transpersonal Studies, 2022)
This paper describes "Kalos, eîdos, skopeîn," an immersive Dhrupad-based dance installation designed to elicit feelings of awe in the spectators, in a real-life artistic context. This study used a mixed-methods approach in order to explore spectators' awe experience (N=45), using specific scales and interpretative phenomenological analysis. Results suggested that "Kalos, eîdos, skopeîn," with its combination of nature motifs and the slow dance-walk associated with the Dhrupad music in the choreography, was able to produce awe-related moments in some spectators and inspire a degree of positive emotions. Our qualitative results viewed awe explicitly as a positive emotion and showed that generally the spectator narratives, involving the whole performance, were based on modified states of consciousness. Three themes emerged: the main theme is "A rich experience of modified states of consciousness" involving the whole performance, and two interconnected sub-themes "Captivated by the slowness of the dancers" associated with the slow movement and "I can still hear the mantra in my head" in rapport with Dhrupad music. This study was carried out as part of the Canadian FRQSC/FCI Project (2019-RC2-260306).